2016
DOI: 10.18632/oncotarget.11800
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 promotes epithelial-mesenchymal transition in hepatocellular carcinoma cells through the activation of PI3K/SGK3/β-catenin signaling pathways

Abstract: Oncogenic mutations in PIK3CA, the gene encoding the catalytic subunit of phosphoinositide 3-kinase (PI3K), occur with high frequency in hepatocellular carcinoma (HCC). The protein kinase Akt is considered to be the primary effector of PI3K, but there is evidence to suggest that serum and glucocorticoid kinase 3 (SGK3) acts in an Akt-independent manner downstream of PI3K. In this report, we found that SGK3 promotes epithelial-mesenchymal transition (EMT) and reduces phosphorylation-dependent degradation of β-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
3
13
1
Order By: Relevance
“…Our previous study confirmed that SGK3 stimulates β-catenin signalling in HCC cells [ 23 ]. It is well established that SGK3 promotes the inactivation of GSK-3β by phosphorylation of GSK-3β on Ser9 [ 22 ].…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Our previous study confirmed that SGK3 stimulates β-catenin signalling in HCC cells [ 23 ]. It is well established that SGK3 promotes the inactivation of GSK-3β by phosphorylation of GSK-3β on Ser9 [ 22 ].…”
Section: Resultssupporting
confidence: 82%
“…The augmentation of Wnt/β-catenin signalling through Ser9 phosphorylation-inactivation of GSK3β is a well-recognised regulatory pathway for CSC self-renewal and cancer development [ 35 , 36 ]. Our previous study confirmed that SGK3 stimulates β-catenin signalling in HCC cells [ 23 ]. Liu et al reported that overexpression of SGK3 increased the phosphorylation level of GSK3-β on Ser9 and inactivates GSK3-β [ 22 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, miR-155 has been reported to target other genes to regulate epithelial–mesenchymal transition (EMT) process. In hepatocellular carcinoma, miR-155 promotes EMT via targeting P85α and TP53INP1 [ 41 , 42 ]. In murine mammary gland epithelial cells, MiR-155 promotes TGF-β-induced EMT via targeting RhoA [ 43 ].…”
Section: Discussionmentioning
confidence: 99%